Tax and transfer system: Considerable redistribution mainly via social insurance - Stefan Bach; Markus Grabka; Erik Tomasch (DIW Economic Bulletin, 2015)
Overall monetary redistribution via the tax and transfer system leads to net incomes being much more evenly distributed in Germany than market income. As a result, in 2011, the Gini coefficient decreased from 0.5 for market income to 0.29 for household disposable income. The social security system has a significant share in total income redistribution by the government, making up more than half of the inequality reduction. As far as there are equivalent insurance contributions for social security benefits, there is, however, no redistribution between individuals or generations over time. This shows that, in terms of how well public transfers are targeted, the most financially needy households are benefitting most from means-tested basic social security payments. Other public benefits such as the child benefit, however, are granted to all income groups. It was primarily the upper income brackets that benefitted from the now expired housing support for owner-occupiers (Eigenheimzulage).
Keywords: H24; H55; D31; 330; redistribution of taxes and transfers; income distribution; SOEP